2020
DOI: 10.14202/vetworld.2020.392-399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding fermented mixture of cassava pulp and Moringa oleifera leaf meal on immune responses, antioxidative status, biochemistry indices, and intestinal ecology of broilers

Abstract: Aim: The study investigated the effect of feeding fermented mixture of cassava pulp and Moringa oleifera leaf meal (FCPMO) on the immune responses, antioxidative status, biochemical parameters, and intestinal ecology of broiler chickens. Materials and Methods: Four hundred Lohmann broiler chickens were distributed to four groups of diets including CONT (corn-soybean-based feed with no additive), BACI (corn-soybean-based diet supplemented with 0.1% zinc bacitracin), FERM (diet containing 20% FCPMO), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…In this study, FPLS seemed to contribute to the increase SOD level of the ICC. This assumption was supported by our previous study showing the increased SOD con- centration in broilers fed with fermented cassava pulp and Moringa oleifera leaf powder (Sugiharto et al, 2020b). Our result showed that HDL level was lower in HSD+mE than those in LSD, HSD, and HSD+FPLS.…”
Section: Serum Sod Mda Biochemical Indices and Antibody Titers Against Ndv Of The Iccsupporting
confidence: 90%
“…In this study, FPLS seemed to contribute to the increase SOD level of the ICC. This assumption was supported by our previous study showing the increased SOD con- centration in broilers fed with fermented cassava pulp and Moringa oleifera leaf powder (Sugiharto et al, 2020b). Our result showed that HDL level was lower in HSD+mE than those in LSD, HSD, and HSD+FPLS.…”
Section: Serum Sod Mda Biochemical Indices and Antibody Titers Against Ndv Of The Iccsupporting
confidence: 90%
“…Taking all the above facts together, the decreased levels of erythrocytes and haemoglobin in additive fed-broilers seemed to be the response of the birds toward the decreased potential of infections. This finding was actually in agreement with Sugiharto et al (2020), reporting the decrease in erythrocytes and haemoglobin levels, concomitant with the decrease in leukocytes and lymphocytes, in broiler chickens when provided with antibiotics, zinc bacitracin, and fermented feed. March 2022 51…”
Section: Complete Blood Counts Of Broilerssupporting
confidence: 92%
“…This value indicates that the total lactic acid bacteria is close to the normal range [12]. [10] stated that the total lactic acid bacteria that grow in the digestive tract of chickens is 4.5 x 10 8 CFU/ml. The addition of 450 ml of sinbiotic resulted in significantly different total microbial colonies with 150 ml and 300 ml administration.…”
Section: Total Microbial Colonies (Tpc) Of Lacticmentioning
confidence: 64%
“…Table 4, it can be seen that the highest mean total microbial colony (TPC) was in the P3 treatment (basal ration + sinbiotic 450 ml/kg ration) which was 3.42 x 10 8 CFU/ml and the lowest average total microbial colony (TPC) was found in P0 (basal ration without sinbiotic) is 2.00 x 10 the total lactic acid bacteria is close to the normal range. [10] stated that the total lactic acid bacteria that grow in the digestive tract of chickens is 4.5 x 10 8 CFU/ml. The addition of 450 ml of sinbiotic resulted in significantly different total microbial colonies with 150 ml and 300 ml administration.…”
Section: Total Microbial Colonies (Tpc) Of Lacticmentioning
confidence: 99%